From Textual to Historical Networks: Social Relations in the Biographical Dictionary of Republican China - Armand, Cécile (Journal of historical network research, 2021)
In this paper, we combine natural language processing (NLP) techniques and network analysis to do a systematic mapping of the individuals mentioned in the Biographical Dictionary of Republican China, in order to make its underlying structure explicit. We depart from previous studies in the distinction we make between the subject of a biography (bionode) and the individuals mentioned in a biography (object-node). We examine whether the bionodes form sociocentric networks based on shared attributes (provincial origin, education, etc.). Our major contribution consists in annotating the links between individuals in order to (1) question the assumption that word cooccurrences equate with actual relations; (2) define a more accurate classification of relationships among elites in republican China. We demonstrate that political and professional relations in this population outweigh the types of social ties commonly accepted in the scholarship on modern China. We eventually develop a method that can be applied to similar corpora in a critical and comparative perspective.